THE FEATURES OF INTERRUPTING, COLLABORATING, AND BACKCHANNELLING USED BY BROADCASTER AND CALLER IN TELEPHONE CONVERSATION - Elok Widiyati (EduLite: Journal of English Education, Literature and Culture, 2016)
Conversational analysis is a part of conversational structure that manages people's communication. It deals with pragmatics. Some of the conversational structures consist of features in interrupting, collaborating, and backchannelling (Celce-Murcia, 1995: 14). This research was intended to analyze how the three features were applied in the English conversation by broadcasters and callers in English Corner Program. This research was qualitative. The data consisted of eight conversations. The data were collected through the following steps: recording, transcribing, selecting, and reporting. Then, they were analyzed with conversational approach drawn on Celce Murcia (1995). It was revealed that the broadcasters and callers in the eight conversations used the features of interrupting, collaborating, and backchanneling. They did not fully perform common English expressions and gambits. However, they tended to perform the simpler and easier ones. This implied that the participants have not known the appropriate expressions. Based on the result of this research, it was concluded that the conversations in this study were less structured and patterned. It was suggested for the readers who learn about conversational structure, that they should pay attention not only to the linguistic components, but also the pragmatics in which the English conversation takes place, including participant, context, and topic of a conversation.